Q. 1 B3.9( 14 Votes )

# In the following,

Answer :

As, p + q = –12

⇒p = –12–q

putting the value of q in other equation,

⇒ pq = 32

⇒ (–12–q)q = 32

⇒–12q–q^{2} = 32

⇒q^{2} + 12q + 32 = 0

⇒q^{2} + 8q + 4q + 32 = 0

⇒q(q + 8) + 4(q + 4) = 0

⇒ (q + 4)(q + 8) = 0

so, q = –4 & q = –8

as, p = –12–q

thus, p = –12 + 4 & p = –12 + 8

p = –8 & p = –4

Rate this question :

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I